Pilates mat versus cervical stabilization exercises on the craniovertebralangle, pain, function, and myoelectrical activity of the cervical musclesin forward head posture: a randomized controlled trial - Elhafez, Haytham M.; Mohammed, Karima S.; Abd El-Azeim, Alshaymaa S.; Abdallah, Ghada A. (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. One of the most prevalent postural problems involving the neck is called forward head posture (FHP), which isdefined as the anterior head protruding from the sagittal plane and appearing to be positioned in front of the body. The incidence of FHP is 70% in young adults. This study aimed to compare Pilates mat versus cervical stabilization exercises on thecraniovertebral angle (CVA), pain, function, and myoelectric activity of the upper trapezius (UT) and sternocleidomastoid (SCM)muscles in patients with FHP. Also, both experimental groups were compared to the control group in terms of CVA, pain, function,and myoelectric activity of the UT and SCM muscles.Methods. Sixty participants (18 to 25 years old) with symptomatic FHP were randomly assigned to three groups using an opaquesealed envelope; Pilates mat and postural correction exercises were assigned group A, cervical stabilization and postural correction exercises were assigned group B, and solely postural correction exercises were assigned group C for 12 weeks at a frequency of 3 times/week. The patients were assessed before and after 12 weeks of interventions. The photogrammetric methodwas used to determine CVA, the visual analog scale (VAS) for pain intensity, the Arabic neck disability index (ANDI) for neckfunction, and surface electromyography (sEMG) for the UT and SCM muscle root mean square during rest and activity.Results. Multiple pairwise comparisons revealed statistically significant differences between pre and post-treatments for allvariables in the Pilates, cervical stabilization, and control groups with a p < 0.05. Between groups, analyses showed that therewere statistically significant differences (p < 0.05) at post-treatment between the Pilates and cervical stabilization groups andalso between Pilates and the control, and finally between the cervical stabilization and control groups with more favor to thePilates group.Conclusions. Pilates mat and cervical stabilization exercises are both effective interventions for FHP, with Pilates mat exercises being superior.
Keywords: Pilates mat; cervical stabilization; postural correction exercises; foreword head posture; muscle amplitude